Prevalence and characterization of positional obstructive sleep apnea with peripheral arterial tonometry in a real-world Colombian cohort - Vanegas-Cadavid, Diego I.; Blanco-Ruíz, Andrés Felipe (Sleep & breathing, 2025)
Purpose Positional obstructive sleep apnea (POSA) is a common but heterogeneous phenotype of obstructive sleep apnea (OSA), and its identification may inform more personalized therapy. This study aims to characterize POSA and non-POSA phenotypes in a real-world cohort using peripheral arterial tonometry-based home sleep apnea testing (PAT-HSAT). Methods A retrospective analysis was performed on adults referred for PAT-HSAT at a single center in Colombia. Subjects were classified as POSA or non-POSA based on standard positional indices. Clinical variables, oxygen desaturation index (ODI4%), time with oxygen saturation below 90% (T < 90), and other sleep metrics were compared between groups. Results The prevalence of POSA varied by classification: Cartwright (38.4%), Levendowski (30.8%), Bignold (21.7%), Mador (7.0%), and APOC Global (46.1%). Significant physiological differences were observed between APOC subgroups. APOC I exhibited the lowest respiratory event indices (pAHI 3%: 10.6 events/h; ODI4%: 5.7 events/h), while APOC III patients showed severe respiratory compromise and hypoxaemia (pAHI 3%: 51.0 events/h; ODI4%: 34.9 events/h; T < 90: 166.8 min; all p < 0.001). Conclusion POSA is prevalent in this Colombian cohort, and the APOC classification effectively captures a broad spectrum of positional phenotypes. Unlike other classification systems, APOC provides a more comprehensive approach to positional characterization. Furthermore, PAT-HSAT emerges as a valid and ecologically alternative tool for postural phenotyping, offering potential for more individualized management of OSA based on positional susceptibility.